Relationship Between National Economic Development and Body Mass Index in Chinese Children and Adolescents Aged 5–19 From 1986 to 2019 - Bu, Te; Popovic, Stevo; Huang, Huiqing; Fu, Tao; Gardasevic, Jovan (Frontiers in Pediatrics, 2021)
Obesity represents a major risk factor for population health. No studies have evaluated how economic expansion impacts the prevalence of obesity. The purpose of this study was to assess the relationship between national economic development and body mass index (BMI) in Chinese children and adolescents. Data of mean BMI in children and adolescents aged 5-19 from 1986 to 2019 were extracted from an international database of cardiometabolic risk factors. Chinese economic development was quantified by the gross domestic product (GDP), which was extracted from the International Monetary Fund. The relationships between GDP and BMI were assessed in 1-year age groups for ages 5–19 years. In addition, the linear regression from the main data and estimated GDP growth allowed the projections of mean BMI for each age group between 2020-2025. The results suggest there was a linear increase in BMI over years, which means that there has been a steady increase in BMI over the economic expansion. Overall, 97% of the variance (Pearson correlation coefficient) of BMI in boys can be explained by the GDP expansion, and the same pattern (98% of the variance) occurred in girls. Projected mean BMI were provided for constructing future national strategies to prevent overweight and obesity in youth. In conclusion, BMI in children and adolescents aged 5-19 trended upwards between 1986-2019. Our analyses for the first time suggest that globalization has a major impact on BMI in China. Economic expansion was highly predictive of BMI increases.